Crystal structure of methyl-N′-[1-(thiophen-2-yl) propylidene] hydrazinecarbodithioate - M. Osman, Uwaisulqarni; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne; Ravoof, Thahira Begum S. A. (Nihon Bunseki Kagakkai, Japan Society for Analytical Chemistry, 2017)
The title compound, C9H12N2S3, was obtained from a condensation reaction between S-methyldithiocarbazate and 1-(2-thienyl)-1-propane. The compound crystallized in the monoclinic space group P21/n with cell parameters a = 10.178(3), b = 13.357(4), c = 8.845(3)Å, β =98.613(5)°, Z = 4 and V = 1188.9(6)Å3. The compound was nearly planar with intermolecular N–H···S hydrogen bonding observed in the crystal lattice.